The Vintage Lifestyle as a Group Identity (Study in Alfred Schutz Phenomenology on Indonesian Pinups Community) - Hamid U, Farid; Oriza Nucifera, Zulviana (International Journal of English Literature and Social Sciences (IJELS), 2019)
Indonesian Pinup Community, commonly known as Indopinups, is a community for women who love Pinup Lifestyle. In their daily lives, Indopinups community members always wear the regional clothing, makeup and vintage hairstyles (an old American culture). This study aims to determine the motives, the meaning of lifestyle and communication behavior of Indopinups community members. The related theories were Alfred Schutz phenomenology theory and Herbert Mead's symbolic interaction theory. This study used a qualitative research approach. The method used was Alfred Schutz Phenomenology. The research participants were 20 people. The techniques of data collection used were in-depth interviews, observation and documentation. The results showed that there are three participants' motives joining the Indopinups community such as, hobby motives, increasing knowledge, and business motives. The mean of Indopinups community for the participants is a sister in passion and lifestyle existence. The mean of a vintage lifestyle for the community members is a valuable culture, the pin up is a lifestyle, is not a cosplay, and it never dies. The communication behavior was carried out by Indopinups community members verbally included a special call for the members and special terms in the genre and pinup style. In addition, the Non-verbally included the appearances (dress style), choice of dress color, and use of attributes such as hats and boots. Besides, the appearance tended to be open and sexy.